The TIP39-PTH2 receptor system: unique peptidergic cell groups in the brainstem and their interactions with central regulatory mechanisms - Dobolyi, Arpád (2009)
Tuberoinfundibular peptide of 39 residues (TIP39) is the recently purified endogenous ligand of the previously orphan G-protein coupled parathyroid hormone 2 receptor (PTH2R). The TIP39-PTH2R system is a unique neuropeptide-receptor system whose localization and functions in the central nervous system are different from any other neuropeptides. TIP39 is expressed in 2 brain regions, the subparafascicular area in the posterior thalamus, and the medial paralemniscal nucleus in the lateral pons. Subparafascicular TIP39 neurons seem to divide into a medial and a lateral cell population in the periventricular gray of the thalamus, and in the posterior intralaminar complex of the thalamus, respectively. Periventricular thalamic TIP39 neurons project mostly to limbic brain regions, the posterior intralaminar thalamic TIP39 neurons to neuroendocrine brain areas, and the medial paralemniscal TIP39 neurons to auditory and other brainstem regions, and the spinal cord. The widely distributed axon terminals of TIP39 neurons have a similar distribution as the PTH2R-containing neurons, and their fibers, providing the anatomical basis of a neuromodulatory action of TIP39. Initial functional studies implicated the TIP39-PTH2R system in nociceptive information processing in the spinal cord, in the regulation of different hypophysiotropic neurons in the hypothalamus, and in the modulation of affective behaviors. Recently developed novel experimental tools including mice with targeted mutations of the TIP39-PTH2R system and specific antagonists of the PTH2R will further facilitate the identification of the specific roles of TIP39 and the PTH2R.